TARAJJI DAN TAMANNI DALAM SAFWAH AL-TAFASIR - Semmang, Syamsuddin; Nursyamsih, Nursyamsih (TAFASIR: Journal of Quranic Studies, 2024)
The objective of this research is to identify the terms "tarajji" and "tamanni" in the tafsir book "Safwah al-Tafasir" by Muhammad Aly al-Sabuni.Data collection was conducted by gathering data from the Quran and the opinions of tafsir scholars on tarajji and tamanni using a tafsir and linguistic approach. The data processing and analysis methods employed were descriptive and inductive.The research findings indicate that tarajji and tamanni are distinguished based on their wording and meaning. In terms of lafaz, tarajji is primarily expressed using the word "la'al" and occasionally with the word "'asa." The word "la'al" and its derivatives appear 129 times, while "'asa" and its derivatives appear 30 times.Tamanni, on the other hand, is expressed using the words "lait" and occasionally "law," "hal," and "ʾala." The word "lait" appears 14 times in the Quran, "law" appears 197 times, and "hal" appears 93 times. Keywords:  Tarajji, Tamanni, Safwah al-Tafasir